Smart Molecularly Imprinted Polymers: Recent Developments and Applications. Issue 11 (26th April 2013) - Ge, Yi; Butler, Benjamin; Mirza, Farhan; Habib‐Ullah, Sabeeh; Fei, Dan
Abstract The use of the molecular imprinting technique to produce polymers with high specificity for a given "molecular template" has undergone a rapid and expansive evolution since the inception of the idea over half a century ago. It was only a matter of time before the seemingly inevitable "marriage" of this concept with another modern research obsession, the generation of "smart" polymers, capable of reacting quickly, accurately and reproducibly to changes in their environment. Many advances have since been made, concerning the quality and diversity of these systems and polymers responsive to temperature, pH and a host of other environmental cues now exist. This article provides a succinct overview of the process and outcomes of "smart" molecular imprinting, followed by a detailed assessment of recent developments and applications in such field.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>